Portrait of Official-Language Minorities in Canada: Francophones in Prince Edward Island - Chavez, Brigitte; Lepage, Jean-François; Bouchard-Coulombe, Camille (Statistics Canada, 2012)
This demolinguistic portrait of the French-speaking population in Prince Edward Island was undertaken with the financial support of Canadian Heritage’s Official Languages Secretariat, Human Resources and Skills Development Canada (HRSDC) and Justice Canada. It is the tenth in a series of demolinguistic portraits of official-language minorities in Canada, prepared by Statistics Canada’s Language Statistics Section. This study paints a general statistical portrait of the official-language minority in Prince Edward Island based on data from the Census of Population and the Survey on the Vitality of Official-Language Minorities in Canada, conducted in 2006. The purpose of such a portrait is to present a set of characteristics, behaviours and perceptions of the minority official-language population, exploiting the analytical opportunities contained in the data. This document is intended to be neither a mere collection of tables nor an in-depth study of the demolinguistic dynamics of the English-speaking population in Prince Edward Island. It presents a range of themes and issues that will be of interest to official-language minorities and anyone concerned with the past, present and future situation of minority official-language populations in Canada. -Section 1 of this demolinguistic portrait concerns the criteria chosen in this study to define Prince Edward Island’s French-speaking population. It also provides a brief description of the data sources used. -Section 2 presents varied information on the evolution of the French-speaking population and its geographic distribution and concentration in Prince Edward Island. This includes an appended map and a detailed table on the size, relative weight and distribution of the Island’s French-speaking population. -Section 3 concerns the main factors that affect or are affected by changes over time in this province’s French-speaking population: transmission of mother tongue and the effect of exogamy; age structure; intragenerational linguistic mobility; and interprovincial migration. It also discusses the use of French in the public sphere and how the ability to conduct a conversation in that language has evolved according to mother-tongue group. -Section 4 looks at a few sectors essential to the vitality of minority official-language communities, as identified in the Roadmap for Canada’s Linguistic Duality 2008–2013: Acting for the Future, namely health, justice, education and the media, the arts and culture. It also provides statistics on community participation, employment and income characteristics, and the use of French at work. -The last section of this portrait presents statistics on the identity of Francophones and their perceptions regarding the presence of French in their community, the provision of federal government services in French, the respect for linguistic rights, and the fact that people are working to develop the Francophone community.